The Nature of School Atmosphere Association to Improve the Students' Personalities in Madrasah Ibtidaiyah (MI) of Kota Langsa - Zulfitri Zulfitri; Mauloeddin Afna Fauzi; Fakhrurrazi Fakhrurrazi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The article scrutinised the nature of primary school atmosphere association to improve students' personalities in Kota Langsa. Kota Langsa has a mixed community background and is located on the eastern coast of Aceh province, which ratifies to perform Islamic Sharia area. The study informants were the people who shared daily interactions with the students, particularly in education performances and religious practices, i.e., the school teachers, parents, village prominent, and religious figures. The article employed a constant comparative method, which examined the conceptual finding of equivalences atmosphere associations. It grounded a theory to explain the phenomena of the nature and nurture of the Islamic primary school environment, when the parents' educational goals, teachers' objectives, and local figures' wisdom meet with the early process of students in their school days. The article proposed the result that confirmed the link between school atmosphere and students' personality development. Finally, the result confirmed the research objective, which described the socio-economic, facility, local figures, and teachers are the main elements to mediate developing students' personalities in Islamic primary school.